Wind-induced vibration of UHV transmission tower line system: Wind tunnel test on aero-elastic model. Issue 171 (December 2017) - Xie, Qiang; Cai, Yunzhu; Xue, Songtao
Abstract: A wind tunnel test on the aero-elastic model of UHV transmission tower line system was carried out for researching tower line system's dynamic behavior under different wind speeds. The effect of wires' vibration on tower was particularly addressed in the paper. For comparison, the single tower model and tower line system model were involved. Both alongwind and crosswind responses of tower were investigated. The wire's dynamic strain was traced synchronously for exploring the coupling vibration effect of tower line system. Comparing the responses of the single tower model and the tower line model, it is found that 70–90% displacement and strain are induced by wires. This action is more prominent in the alongwind direction. However, the peak response values of the tower line model are smaller than those of the single tower model. Test results in frequency domain indicate that the dynamic behavior of the tower becomes more susceptible to wind speed when it connects with wires. As to the tower line system, the response power spectra of the tower and the conductors show the tendency of moving to lower and higher frequency region respectively with the crests weakened and vibration energy dispersed when wind speed increases. Highlights: Wind tunnel test on the aero-elastic model of tower line system was carried out. Alongwind and crosswind responses of the tower are investigated. Peak responses of tower line model are smaller than those of single tower model. Dynamic behavior of tower is more susceptible to wind when it connects with wires. Response PSD of tower and conductor shows opposite rules when wind speed increases.